Brain functional correlates of emotional face processing in body dysmorphic disorder. (March 2022) - Borgers, Tiana; Kürten, Marla; Kappelhoff, Anna; Enneking, Verena; Möllmann, Anne; Schulte, Johanna; Klug, Melissa; Leehr, Elisabeth J.; Dohm, Katharina; Grotegerd, Dominik; Krause, Philine; Zwiky, Esther; et al.
Abstract: Previous neuroimaging studies in body dysmorphic disorder (BDD) have focused on discordances in visual processing systems. However, little is known about brain functional aberrations in individuals with BDD during emotional face processing. An fMRI paradigm with negative emotional faces was employed in 20 individuals with BDD and 43 mentally healthy controls (HC). We compared functional activity and whole-brain connectivity patterns of the amygdala and the fusiform gyrus (FFG) between both groups. Regression analyses were performed for associations of body dysmorphic symptoms with brain activity and connectivity. Individuals with BDD exhibited higher activity in the left amygdala compared to HC ( p FWE = .04) as well as increased functional connectivity of the left amygdala with a network including frontostriatal and temporal regions ( p FWE < .05). The FFG revealed increased functional connectivity in individuals with BDD, mapping to brain areas such as the cingulate cortex and temporo-limbic regions ( p FWE < .05). In HC, higher levels of body dysmorphic symptoms were associated with higher functional amygdala and FFG activity ( p FWE < .05). Individuals with BDD show aberrant functional activity and connectivity patterns within the amygdala and the FFG for negative emotional face processing. Body dysmorphic symptoms in HC are associated with a mild pattern of brain functional alterations, which could emphasize the relevance of a dimensional approach in addition to diagnosis. Treatments for BDD could benefit from targeting visual misperception and evaluation processes upon confrontation with emotional information. Highlights: BDD shows amygdala hyperactivity during negative emotional face processing. BDD shows amygdala and FFG hyperconnectivity with frontostriatal and temporal areas. Body dysmorphic symptoms are associated with higher amygdala and FFG activity in HC.